2018
DOI: 10.3892/or.2018.6900
|View full text |Cite
|
Sign up to set email alerts
|

lincRNA‑p21 inhibits the progression of non‑small cell lung cancer via targeting miR‑17‑5p

Abstract: Non-small-cell lung cancer (NSCLC) is well established as one of the major subtypes of human lung cancer. NSCLC is characterized by a high incidence rate and poor patient prognosis. Previous studies have identified that long intergenic non-coding RNA (lincRNA) serves a key role in the development of tumor and malignant metastasis. However, the majority of the underlying mechanisms for lincRNA deregulation in various diseases, including cancer and diabetes, have not been completely elucidated. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Recently, many studies have supported a novel regulatory mechanism of lncRNA in human cancers, mainly represented by the interaction between lncRNA and miRNA. LncRNA can act as a ceRNA or molecular sponge to regulate miRNA expression and regulate the occurrence and progression of many cancers (Tu et al, 2019;Ao et al, 2019;Yu et al, 2019). For example, lncRNA Unigene 56159 promotes the epithelial-mesenchymal transition of hepatoma cells by acting as a ceRNA of miR-140-5p (Lv et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have supported a novel regulatory mechanism of lncRNA in human cancers, mainly represented by the interaction between lncRNA and miRNA. LncRNA can act as a ceRNA or molecular sponge to regulate miRNA expression and regulate the occurrence and progression of many cancers (Tu et al, 2019;Ao et al, 2019;Yu et al, 2019). For example, lncRNA Unigene 56159 promotes the epithelial-mesenchymal transition of hepatoma cells by acting as a ceRNA of miR-140-5p (Lv et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To date, lncRNA/miRNA axis has been a limelight in the field of cancer. LncRNA can trap miRNA, regulate mRNA, and modulate progression of various cancers ( Ao et al, 2019 ; Tu et al, 2019 ). This paper verified miR-301b-3p/ADAMTS9-AS1/TGFBR2 interaction by bioinformatics method, RIP and dual luciferase assay.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant investigations have revealed that lncRNAs regulate tumor progression via regulation of miRNAs 23–25 . Interestingly, the present study revealed that miR‐130b‐3p and miR‐301b‐3p was related to CASC19 and was up‐regulated under CASC19 knockdown.…”
Section: Discussionmentioning
confidence: 52%